Biological Functions Driven by mRNAs Carried by Extracellular Vesicles in Cancer - Prieto-Vila, Marta; Yoshioka, Yusuke; Ochiya, Takahiro (Frontiers in Cell and Developmental Biology, 2021)
Extracellular vesicles (EVs), including exosomes and microvesicles, are extracellular nanovesicles released by most cells. EVs play essential roles in intercellular communication via the transport of a large variety of lipids, proteins, and nucleic acids to recipient cells. Nucleic acids are the most commonly found molecules inside EVs, and due to their small size, microRNAs and other small RNAs are the most abundant nucleic acids. However, longer molecules, such as mRNAs, have also been found. mRNAs encapsulated within EVs have been shown to be transferred to recipient cells and translated into proteins, altering the behavior of the cells. Secretion of EVs is maintained not only through multiple normal physiological conditions but also during aberrant pathological conditions, including cancer. Recently, the mRNAs carried by EVs in cancer have attracted great interest due to their broad roles in tumor progression and microenvironmental remodeling. This review focuses on the biological functions driven by mRNAs carried in EVs in cancer, which include supporting tumor progression by activating cancer cell growth, migration and invasion; inducing microenvironmental remodeling via hypoxia, angiogenesis, and immunosuppression; and promoting modulation of the microenvironment at distant sites for the generation of a premetastatic niche, collectively inducing metastasis. Furthermore, we describe the potential use of mRNAs carried by EVs as a noninvasive diagnostic tool and novel therapeutic approach.